Provisional Verbatim Record of the Eight Hundred and Forty-Ninth Plenary Meeting. Fourteenth Session, A/P 848 - Héderváry, Claire de (1959)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations. General Assembly US representative makes a deeply moving speech in defense of the Hungarian revolution. Accuses Hungarian government of not letting up on the persecutions, death sentences and executions of Hungarians, especially the young people who participated in the 1956 uprising. He calls Hungary a "house without windows" referring to the barbed wire being built along the border with Austria and Yugoslavia.